Antimicrobial and Antimycobacterial Activity of Some Quinoxalines ’N’ Bridgehead Heterocycles - GANAPATY, S.; RAMALINGAM, P.; BABURAO, CH. (Asian Journal of Chemistry, 2010)
Quinoxalin-2,3-diones (1) on treatment with o-phenylenediamine afforded 6,11-dihydro-5,6,-11,12-tetraazanaphthacene (3). 2,3-Dichloroquinoxaline (2) on condensation with anthranilic acid, o-phenylenediamine and sodium azide yielded bis[quinazolino(3,2a)quinoxaline]-11,18-diones (4), bis[benzimidazolo( 1,2a)quinoxaline] (5) and bis-[1,2,3,4-tetrazolo (1,5a)quinoxaline] (6), respectively. The structures have been established by IR, mass spectral and elemental analysis. These compounds have been evaluated for their antibacterial, antifungal and antitubercular activity.